Influence of sire and sire breed (Gyr versus Holstein) on establishment of pregnancy and embryonic loss in lactating Holstein cows during summer heat stress - Pegorer, Marcelo F.; Vasconcelos, José Luiz Moraes [UNESP]; Trinca, Luzia A.; Hansen, Peter J.; Barros, Ciro M. (Elsevier B.V., 2007)
Heat stress has negative effects on pregnancy rates of lactating dairy cattle. There are genetic differences in tolerance to heat stress; Bos taurus indicus (B. t. indicus) cattle and embryos are more thermotolerant than Bos taurus taurus (B. t. taurus). In the present study, the effects of sire and sire breed on conception and embryonic/fetal loss rates of lactating Holstein cows during the Brazilian summer were determined. In Experiment 1, cows (n = 302) were AI after estrus detection or at a fixed-time with semen from one Gyr (B. t. indicus) or one Holstein sire (B. t. taurus). Pregnancy was diagnosed 80 days after AI. In Experiment 2, cows (n = 811) were AI with semen from three Gyr and two Holstein sires. Pregnancy was diagnosed at 30-40 and at 60-80 days after AI. Cows diagnosed pregnant at the first examination but non-pregnant at the second were considered as having lost their embryo or fetus. Data were analyzed by logistic regression. The model considered the effect of sire within breed, sire breed, days postpartum, period of lactation, and AI type (AI after estrus versus fixed-time). There was no effect of the AI type, days postpartum or milk production on conception or embryonic loss rates. The use of Gyr bulls increased pregnancy rate when compared to Holstein bulls [9.1% (60/657) versus 5.0% (23/456), respectively, P = 0.008; data from Experiments 1 and 2 combined]. Additionally, in Experiment 2, cows inseminated using semen from sire #4 (Gyr) had lower embryonic loss (10%) when compared with other B. t. indicus (35.3% and 40%) or B. t. taurus sires (18.2% and 38.5%, P = 0.03). In conclusion, the use of B. t. indicus sires may result in higher conception rates in lactating Holstein cows during summer heat stress. Moreover, sire can affect embryonic loss and selection of bulls according to this criterion may result in higher parturition rates in lactating Holstein cows. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: heat stress; artificial insemination; pregnancy; Bos indicus; Bos taurus